2009
DOI: 10.1021/jp906665j
|View full text |Cite
|
Sign up to set email alerts
|

Control of Exciton Migration Efficiency in Disordered J-Aggregates

Abstract: Using luminescent exciton traps, an efficiency of the exciton migration in J-aggregates of an amphiphilic analogue of pseudoisocyanine (amphi-PIC) dye in solutions, has been investigated. Applying a modified Stern−Volmer equation for analysis of the J-aggregate luminescence quenching by the trap, the quenching of 50% of amphi-PIC J-aggregate luminescence accessible for trapping at the ratio amphi-PIC/DiD = 120:1 has been revealed. To increase the exciton migration efficiency, the J-aggregate structure was impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…These rings are composed from 25-30 dye molecules [15]. As was shown earlier, the exciton ST in amphi-PIC J-aggregates strongly depends on the static disorder degree which can be changed, by varying the water content in a DMF=water binary solution [12][13][14]16].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These rings are composed from 25-30 dye molecules [15]. As was shown earlier, the exciton ST in amphi-PIC J-aggregates strongly depends on the static disorder degree which can be changed, by varying the water content in a DMF=water binary solution [12][13][14]16].…”
Section: Resultsmentioning
confidence: 93%
“…Recently, we have shown that the presence of cationic surfactant CPB in a DMF=water binary solution at room temperatures causes drastic changes in the optical properties of amphi-PIC J-aggregate: the J-band intensity increases, the J-band becomes narrow, the value of N del grows (from 4 monomers in solutions without CPB up to 11 monomers in solutions with CPB), and the luminescence quantum yield increases slightly (from 0.3 up to 0.5) [15]. In a frozen matrix at the liquid nitrogen temperature, the CPB addition causes the same effect: the J-band becomes more intense and narrower (Dn FWHM ¼ 415 cm À1 as compared with Dn CPB FWHM ¼ 320 cm À1 ) and shifts to a longer wavelength (from k max ¼ 579 nm to k CPB max ¼ 580.5 nm) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By estimating Δν fwhm mon = 1220 cm −1 for the main electronic transition of the TC monomer band ( Figure 1, the blue dashed curve), we obtain N c ≈ 4 monomers similarly to the case of strongly disordered amphi-PIC J-aggregates. 26,27 It should be noted that the fluorescence decay curve of TC J-aggregates appeared to be very short with the lifetime less than 20 ps, and consequently, it could not be correctly resolved with our lifetime instrument (see Supporting Information Figure S2). Hence, in the present work the lifetime changes have not been analyzed.…”
Section: ■ Resultsmentioning
confidence: 99%
“…[10, 11b] In addition, the aggregation defect (exciton trap) due to molecular displacement introduces nonradiative loss of photoexcitation energy. [12] These factors collectively restrict porphyrin antenna functionality for interfacial charge-separation phenomenon which also take place in the ultrafast time domain. [13] As a result, porphyrin aggregates are less studied [7,14] due to the complicacy of exciton sensitization.…”
Section: Introductionmentioning
confidence: 99%